Exploring the use of online social networking by employees: Looking at the potential for information leakage - Abdul Molok, Nurul Nuha; Ahmad, Atif; Chang, Shanton (2011)
The proliferation of online social networking (OSN) in recent years has caused organizations information security threats due to disclosure of information by their employees on their sites. The accessibility of OSN to anyone, at any time, using any devices, causes confidential and sensitive organizational information to be disclosed to unauthorised individuals, whether accidentally or intentionally. This study aims to explore this current phenomenon by investigating OSN use behaviour among employees that leads to information leakage through the lens of Decomposed Theory of Planned Behavior. It also seeks to investigate the strategies utilized by organizations to control such use and propose a control framework that effectively safeguards organizational information security from this threat.